Antimicrobial Resistance in Wildlife in Guadeloupe (French West Indies): Distribution of a Single blaCTX–M–1/IncI1/ST3 Plasmid Among Humans and Wild Animals - Guyomard-Rabenirina, Stephanie; Reynaud, Yann; Pot, Matthieu; Albina, Emmanuel; Couvin, David; Ducat, Celia; Gruel, Gaëlle; Ferdinand, Severine; Legreneur, Pierre; Le Hello, Simon; Malpote, Edith; Sadikalay, Syndia; et al. (Frontiers in Microbiology, 2020)
Limited data are available on the contribution of wildlife to the spread of antibacterial resistance. We determined the prevalence of resistance to antibiotics in Escherichia coli isolates collected from wild animals in 2013 and 2014 and the genetic basis for resistance to third-generation cephalosporin in Guadeloupe. We recovered 52 antibiotic-resistant (AR) E. coli strains from 48 of the 884 (5.4%) wild animals tested (46 iguanas, 181 birds, 289 anoles and 368 rodents at 163 sampling sites). Rodents had higher rates of carriage (n=38, 10.3%) than reptiles and birds (2.4% and 1.1%, respectively, p < 0.001). A significant association (p < 0.001) was found between the degree of anthropization and the frequency of AR E. coli carriage for all species. The carriage rate of ciprofloxacin- and cefotaxime-resistant isolates was 0.7% (6/884) and 1.5% (13/884), respectively. Most (65.4%) AR E. coli were multi-drug resistant, and the prevalence of extended-spectrum beta-lactamase (ESBL)-producing E. coli was low (n=7, 0.8%) in all species. Eight ESBL-producing E. coli were recovered, 2 genetically unrelated isolates being found in 1 bird. These isolates and 20 human invasive ESBL E. coli isolates collected in Guadeloupe during the same period were investigated by whole genome sequencing. blaCTX-M-1 was the only ESBL gene shared by 3 animal classes (humans, n=2; birds, n=2; rodents, n=2). The blaCTX-M-1 gene and most of the antimicrobial resistance genes were present in a large conjugative IncI1 plasmid that was highly similar (> 99% nucleotide identity) to ESBL-carrying plasmids found in several countries in Europe and in Australia. Although the prevalence of ESBL-producing E. coli isolates was very low in wild animals, it is of concern that the well-conserved IncI1 plasmid-carrying blaCTX-M-1 is widespread and occurs in various E. coli strains from animals and humans.